Сучасні інвестиційні механізми фінансування проектів у будівництві - Костенко, С. В. (Ways to Improve Construction Efficiency, 2012)
A variety of ways to invest building today is an occasion for a detailed analysis of the financial and credit mechanisms. Selection of optimal financing schemes and tax planning in the implementation of construction projects is the key to efficiency and profit from the activity.